Drug repurposing: a new front in the war against Staphylococcus aureus. (August 2016) - Das, Swetarka; Dasgupta, Arunava; Chopra, Sidharth
Staphylococcus aureus continues its domination of worldwide bacterial infection rates, thereby remaining a pathogen of significant public health interest. A major reason for its continued success is its ability to acquire and maintain diverse drug resistance mechanisms, leading to a paucity of antimicrobials active against it, concomitantly leading to a continuous search for new antimicrobial agents. However, with the withdrawal of the major pharmaceutical firms from the anti-infective area, drug repurposing has provided a potential boost to the drug pipeline. In this review, we provide an overview of the currently approved drugs with repurposing potential against Staphylococcus aureus, thus augmenting the classical drug discovery pathway.